QOLP-15. QUALITATIVE STUDY OF DIFFERENTIAL QUALITY OF LIFE (QOL) IN SUPRASELLAR MENINGIOMA PATIENTS TREATED VIA ENDOSCOPIC ENDONASAL APPROACH VERSUS OPEN CRANIOTOMY. (9th November 2020) - Khalafallah, Adham; Fung, Shirley; Kozachik, Sharon; Valappil, Benita; Shaar, Hussam Abou Al; Wang, Eric; Zenonos, Georgios; Snyderman, Carl; Gardner, Paul; Gallia, Gary; Rowan, Nicholas; Mukherjee, Debraj
Abstract: BACKGROUND: The optimal surgical treatment of suprasellar meningiomas remains controversial. While successful surgery has historically been measured by extent of tumor resection (EOR), surgeons must also balance tumor- and patient-specific characteristics with quality of life (QoL) outcomes when considering either an open craniotomy or endoscopic endonasal approach (EEA). METHODS: We conducted 28 in-depth individual interviews with patients diagnosed with suprasellar meningioma and treated via EEA (n=14) or craniotomy (n=14). We used a structured interview script and the transcribed interviews were independently coded by two researchers. Consensus was used to identify themes and domains of interest. RESULTS: The overall sample (80% between 40-69 years old, 70% female, and 82% white) was largely similar between craniotomy and EEA cohorts. Tumor volumes were not different between both cohorts (p=0.2), with a combined average of 4.4 cm 3 (standard error ± 0.7). Suprasellar meningiomas caused a wide range of symptoms with 21 concepts elicited. The most frequently endorsed concepts were "Vision" (n=22), "Headaches" (n=11), "Fatigue" (n=11), "Cognitive Symptoms" (n=10), "Pituitary Dysfunction – including Trouble Sleeping and Frequent Urination" (n=9), "Sinus Problems" (n=7), and "Personality Changes" (5). Both surgical approaches demonstrated improvements in vision (69.2% EEA, 66.7% craniotomy) and headaches (100% EEA, 80% craniotomy). Compared to EEA, craniotomy yielded a longer list of complications (3 vs.14) and surgery-specific symptoms (9 vs.16). More craniotomy patients reported having negative emotions (5 vs.1), new depression and anxiety (6 vs.1), financial difficulties (3 vs.1), and reduced desire/ability to pursue fun activities (12 vs.7) after surgery relative to EEA counterparts. CONCLUSION: Suprasellar meningiomas can be debilitating with significantly impact on patients' health and QoL. Our findings demonstrate differential effects upon patients' post-operative QoL associated with type of surgery. Our findings support the need for measuring patient-centered, disease-specific QoL outcomes in patients undergoing craniotomy versus EEA for suprasellar meningioma resection.